A Pragma-stylistic Analysis of Hesitation and Repair in the Language of Trauma inside the Courtroom - Hajir Mahmood Ibrahim Alallo; Sarab Khalil Al-Azzawi (مجلة الباحث, 2025)
Abuse survivors might find it difficult to speak about their experience, especially if it must be presented in public. This difficulty is reflected in their language and is at its highest when dealing with severe abuse such as violence, life-threatening incidents, assaults, or defamation. In light of this, post-traumatic speakers produce identifiable linguistic patterns that lead to the intensity of the situation. Despite rich research on trauma in different fields, there is a gap in studying the trauma discourse from a Pragma-stylistic perspective. Accordingly, the study aims to fill this gap and explore the pragmatic and stylistic markers of hesitation, ways of repair, and avoidance strategies employed in courtroom testimony. Considering the nature of the study's main objectives, the selected data consists of courtroom testimonies during the direct examination of the well-known televised trial of the Menendez Brothers. The study focuses on the language of the two brothers during their narration of a sequence of events that led to the murder of their parents. To achieve these aims, the study analyses key features of spoken language, including hesitations, pauses, and repetition, drawing on Tissi’s (2000) framework for pauses and Stenstrom’s (2012) model of disfluencies. Moreover, the study reaches several conclusions, among which is that fillers are a distinct marker of trauma, and they serve both cognitive and interpersonal functions. In other words, they are either used to soften the intensity of the emotional load or they maintain the flow of the conversation.